Biomechanical analyses of prosthetic mesh repair in a hiatal hernia model. Issue 7 (6th March 2014) - Alizai, Patrick Hamid; Schmid, Sofie; Otto, Jens; Klink, Christian Daniel; Roeth, Anjali; Nolting, Jochen; Neumann, Ulf Peter; Klinge, Uwe
Abstract Recurrence rate of hiatal hernia can be reduced with prosthetic mesh repair; however, type and shape of the mesh are still a matter of controversy. The purpose of this study was to investigate the biomechanical properties of four conventional meshes: pure polypropylene mesh (PP‐P), polypropylene/poliglecaprone mesh (PP‐U), polyvinylidenefluoride/polypropylene mesh (PVDF‐I), and pure polyvinylidenefluoride mesh (PVDF‐S). Meshes were tested either in warp direction (parallel to production direction) or perpendicular to the warp direction. A Zwick testing machine was used to measure elasticity and effective porosity of the textile probes. Stretching of the meshes in warp direction required forces that were up to 85‐fold higher than the same elongation in perpendicular direction. Stretch stress led to loss of effective porosity in most meshes, except for PVDF‐S. Biomechanical impact of the mesh was additionally evaluated in a hiatal hernia model. The different meshes were used either as rectangular patches or as circular meshes. Circular meshes led to a significant reinforcement of the hiatus, largely unaffected by the orientation of the warp fibers. In contrast, rectangular meshes provided a significant reinforcement only when warp fibers ran perpendicular to the crura. Anisotropic elasticity of prosthetic meshes should therefore be considered in hiatal closure with rectangular patches. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1485–1495, 2014.